Hubungan Dukungan Keluarga dan Efikasi Diri dengan Motivasi Lansia Hipertensi Dalam Mengontrol Tekanan Darah - Br.Siahaan, Resty Hoky; Utomo, Wasisto; Herlina, Herlina (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: Family support and self-efficacy are ways to increase the motivation of the elderly to control their blood pressure regularly. This study aims to determine the relationship between family support and self-efficacy with the motivation of elderly hypertension in controlling blood pressure.Methods: The variables in this study were the relationship between family support and the motivation of the elderly with hypertension in controlling blood pressure and the relationship between self-efficacy and the motivation of the elderly in controlling blood pressure. This study used a descriptive correlation design with a cross sectional approach. The research sample was 65 elderly who were taken using the snowball sampling method. The analysis used bivariate analysis using chi-square test.Results: There were 36 respondents (55.4%) who received high family support to control blood pressure. Based on self-efficacy, 34 respondents (52.3%) had high self-efficacy in controlling blood pressure. Based on motivation, there are 40 respondents (61.5%) who have high motivation in controlling blood pressure. The results of statistical tests showed that there was a significant relationship between family support and the motivation of the elderly with hypertension in controlling blood pressure with p value (0.001) < alpha (0.05), while the self-efficacy variable with the motivation of the elderly in controlling blood pressure obtained p value (0.000) < alpha (0.05).Conclusion: Family support and self-efficacy have a significant relationship to the motivation of the elderly in controlling blood pressure.